Bat habitat requirements : implications for land use planning - Wermundsen, Terhi (2010)
Knowledge of the habitat requirements of bat species is needed in decision making in land use planning. Bats' hibernation requirements were studied both in Estonia and in southern Finland. In both countries, the northern bat and the brown long-eared bat hibernated in colder and drier locations, whereas Daubenton's bat and Brandt's/whiskered bats hibernated in warmer and more humid locations. In Estonia, the pond bat hibernated in the warmest and most humid conditions, whereas Natterer's bat hibernated in the coldest and driest conditions. Hibernacula were at their coldest in mid-season and became warmer towards the end of the season. The results suggest that bats made an active choice of colder hibernation temperatures at the seasons end. They minimised the negative effects of hibernation early in the hibernation season by hibernating in warmer locations and energy expenditure late in the hibernation season by hibernating in colder locations. The use of foraging habitats was studied in northern and southern Finland. The northern bat used foraging sites opportunistically. Daubenton's bat foraged mainly in water habitats, whereas Brandt's/whiskered bats and the brown long-eared bat foraged mainly in forest habitats. In northern Finland, Daubenton's bats foraged almost exclusively on rivers and typically together with the northern bat. Daubenton's bats and Brandt's/whiskered bats were found only where there were lower ambient light levels. One of the most important things in the management of foraging areas for them is to keep them shady. Hibernacula in Finland typically housed few bats, suggesting that hibernation sites used by even a small number of bats are important. Bats typically used natural stone for hibernation suggesting that natural underground sites in rocks or cliffs or man-made underground sites built using natural stone are important for them. The results suggest that appropriate timing of surveys may vary according to the species and latitude. Lepakot ovat tiukasti suojeltuja koko Euroopan Unionin ...